2016
DOI: 10.1007/s11356-016-6941-5
|View full text |Cite
|
Sign up to set email alerts
|

Variations in organic carbon, aggregation, and enzyme activities of gangue-fly ash-reconstructed soils with sludge and arbuscular mycorrhizal fungi during 6-year reclamation

Abstract: Mining activities can cause drastic disturbances in soil properties, which adversely affect the nutrient cycling and soil environment. As a result, many efforts have been made to explore suitable reclamation strategies that can be applied to accelerate ecology restoration. In this study, we reconstructed mine soils with fly ash, gangue, sludge, planted ryegrass, and inoculated arbuscular mycorrhizal fungi (AMF) in Pangzhuang mine of Xuzhou during 2009 to 2015. The soil aggregation process, enzyme activities (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…Very rare research reports are available in the literature demonstrating the role of AMF in mitigation of combined effects of two or more stresses. AMF symbiosis protects plants against a variety of abiotic stresses using various processes such as improved photosynthetic rate, uptake and accumulation of mineral nutrients, accumulation of osmoprotectants, up-regulation of antioxidant enzyme activity, and change in the rhizosphere ecosystem (Bárzana et al, 2015; Calvo-Polanco et al, 2016; Yin et al, 2016). Several studies have shown improved nutritional status of AMF plants under osmotic stress conditions (Augé et al, 2014; Lehmann et al, 2014; Lehmann and Rillig, 2015) resulting from deficit irrigation or salinity.…”
Section: Amf and Combined Abiotic Stressesmentioning
confidence: 99%
“…Very rare research reports are available in the literature demonstrating the role of AMF in mitigation of combined effects of two or more stresses. AMF symbiosis protects plants against a variety of abiotic stresses using various processes such as improved photosynthetic rate, uptake and accumulation of mineral nutrients, accumulation of osmoprotectants, up-regulation of antioxidant enzyme activity, and change in the rhizosphere ecosystem (Bárzana et al, 2015; Calvo-Polanco et al, 2016; Yin et al, 2016). Several studies have shown improved nutritional status of AMF plants under osmotic stress conditions (Augé et al, 2014; Lehmann et al, 2014; Lehmann and Rillig, 2015) resulting from deficit irrigation or salinity.…”
Section: Amf and Combined Abiotic Stressesmentioning
confidence: 99%
“…Trace elements like Mn and Cu were still not restricted significantly, in future works, more trace elements, more proportioning of backfill materials from different coalmines should be tested. Yin et al reported by using flay ash in reclamation, it could have influence on physical structure of reconstructed overlaying soil, by using sludge and fungi could restore the soil aggregations and the soil organic carbon [ 6 ]. Therefore in future studies we should also considered the optimization of soil quality, at the same time of contamination control.…”
Section: Discussionmentioning
confidence: 99%
“…At present, in China there are about 4.5 billion tons of coalmine solid wastes are stored in dumps: worse still is that the dumps keep increasing around 0.95 billion tons/year. At present, there are totally about 1500 coalmine waste dumps in China, which occupy more than 8 × 10 4 hm 2 land areas [ 5 , 6 , 7 , 8 , 9 ]. Mining subsidence and dumps destroy land resources and make them to be unavailable for any uses.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations